Studies on renal basement membranes - Cotter, T; Cotter, Thomas Gerard (1979)
A novel method is developed for studying the filtration properties of renal basement membranes in vitro and is used to examine how the phenomenon of 'concentration polarisation' effects the filtration of a number of protein solutions through a film of basement membrane. The permeability of the membrane film was dependent, not only on the membrane pore size, but also on the filtration conditions and the solutes being filtered. Large molecules, which failed to pass through the basement membrane film, effectively increased its retentivity to small solute molecules by acting as a secondary barrier to filtration. Polarisation effects can also cause a dramatic increase in solute flux through the membrane film; an effect which is enhanced by increased pressure, decreased stirring speed and the absence of non-permeable molecules from the solutions being filtered. A serine proteinase was purified from the granules of rabbit polyraorphonuclear leucocytes, which hydrolysed NBA a synthetic substrate for elastase, but which failed to exhibit any elastolytic activity. The proteinase had a molecular weight of 26,000, and was judged to be homogeneous from sodium dodecyl sulphate and isoelectric focusing gel electrophoresis. Analysis by ultracentrifugation demonstrated that the proteinase formed dimers and tetramers, associations which were more pronounced at 21°C than at 4°C. The enzyme exhibited a broad substrate specificity, capable of hydrolysing a number of proteins including basement membrane. A second proteinase capable of hydrolysing basement membrane, but not other substrates tried, was partially characterised. From gel electrophoresis it appeared to have a molecular weight less than 12,000 and was highly basic. The ability of a number of proteinases, including the purified NBA esterase, to degrade basement membrane and alter its porosity was examined. Trypsin and collagenase rapidly degraded basement membrane and increased its permeability to a number of pure proteins as well as serum. NBA esterase released up to 12 % of basement membrane protein and increased the permeability of the membrane to a number of test solutes. The physiological and pathological significance of the effects of concentration polarisation and proteolytic mediated alterations in basement membrame porosity are discussed.